THE IMPACT OF CELEBRITY ENDORSEMENT ON CONSUMER BEHAVIOR WITHIN THE SHOPEE ONLINE SHOPPING PLATFORM - Muhammad Ivan Syaugy; Dewi Wuisan (Universitas Pelita Harapan, 2023)
This study aims to investigate the impact of celebrity endorsement on consumer behavior in the Shopee marketplace. The research employed a quantitative approach and collected data through an electronic questionnaire using Google Forms, with a total of 160 respondents from Indonesian consumers living in Greater Jakarta who have seen Shopee advertisements and shopped in the marketplace. Validity and reliability tests were performed in the measurement model, while the R-square test, T-statistics, and P-value tests were utilized in the structural model to evaluate the relationship among the variables. The results suggest that the attractiveness of celebrity endorsers does not significantly affect ad recall by consumers, whereas the credibility of the endorser has a significant impact on both ad recall and purchase intention of consumers.Bahasa Indonesia Abstrak: Penelitian ini bertujuan untuk meneliti dampak dari dukungan selebriti pada perilaku konsumen di pasar Shopee. Penelitian ini menggunakan pendekatan kuantitatif dan mengumpulkan data melalui kuesioner elektronik menggunakan Google Forms, dengan total 160 responden dari konsumen Indonesia yang tinggal di Jakarta yang telah melihat iklan Shopee dan berbelanja di pasar. Uji validitas dan reliabilitas dilakukan dalam model pengukuran, sementara uji R-square, T-statistik, dan nilai P digunakan dalam model struktural untuk mengevaluasi hubungan antara variabel-variabel. Hasilnya menunjukkan bahwa daya tarik dukungan selebriti tidak berpengaruh signifikan pada ingatan iklan oleh konsumen, sedangkan kredibilitas endorser berdampak signifikan pada ingatan iklan dan niat beli konsumen.